Assessment of nutritional, antioxidant, and antidiabetic properties of the BF 1 herbal formulation via in vitro and ex vivo approaches (Kuwait Journal of Science)
The study investigated the dietary composition of the BF1 herbal formulation and its effect on carbohydrate hydrolyzing enzymes linked with type 2 diabetes (α-amylase and α-glucosidase enzymes) through in vitro and ex vivo parameters. In vitro antioxidant parameters, such as 1,1-diphenylhydraxyl (DPPH), Fe2+ chelating abilities, ferric reducing antioxidant property (FRAP), hydroxyl (OH) scavenging, and nitric oxide (NO), as well as ex vivo parameters, such as glutathione (GSH), malondialdehyde (MDA) level, and catalase, ENTPDase, and ATPase enzyme activities in iron-induced pancreatic injury were evaluated. The inhibitory assay for α-amylase and α-glucosidase enzymes was conducted and the results of these parameters revealed that the BF1 formulation could scavenge DPPH radicals compared to the control. At all concentrations, the BF1 formulation reduced ferric compounds, compared to the standard. The BF1 formulation chelated iron better at its lower concentration, similar to the control. Additionally, the BF1 formulation showcased a significant NO radical scavenging ability in comparison to the standard. The BF1 formulation reduced lipid peroxidation in the rat pancreas at a lower concentration than the control. Furthermore, the BF1 formulation demonstrated significant inhibition of α-amylase and α-glucosidase in comparison to the control (metformin). This suggests that BF1 formulation can be considered a potential antidiabetic treatment and can be used for supplement formulation. © 2025 The Authors